2014
DOI: 10.5296/jmr.v6i4.6318
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Pay Satisfaction: Examining the Relationship of a Sample of Blue Collar Workers Personality and Their Pay Satisfaction Levels

Abstract: Compensation plans are the tool that unites employers and employees together in one of the most important exchange processes that happens in organizations. Pay satisfaction is usually achieved when employees feel that they are being paid fairly compared to their referent others. It is desirable for organizations to enhance employee pay satisfaction because it can enhance productivity and commitment to the organization. This study addressed the pay satisfaction process by analyzing the relationship of personali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…For example, in the United States, Scott et al 16 confirmed that the structures, programs and policies of total rewards influence the participation of employees. Nielson and Smith 17 distinguished a relationship between the salary satisfaction of "blue collar workers," which occurs when employees feel that they are paid fairly, compared with others, and consequently improve productivity and commitment to the organization. In Mexico, Zambada and Madero 18 identified that internal wage equity is one of the most significant variables in predicting the intention to remain in employment.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the United States, Scott et al 16 confirmed that the structures, programs and policies of total rewards influence the participation of employees. Nielson and Smith 17 distinguished a relationship between the salary satisfaction of "blue collar workers," which occurs when employees feel that they are paid fairly, compared with others, and consequently improve productivity and commitment to the organization. In Mexico, Zambada and Madero 18 identified that internal wage equity is one of the most significant variables in predicting the intention to remain in employment.…”
Section: Introductionmentioning
confidence: 99%